Elizabeth Stuart Phelps : Selected Tales, Essays, and Poems - Phelps, Elizabeth Stuart, 1844-1911 (Book collections on Project MUSE., 2014)
"The well-educated daughter of a minister, Elizabeth Stuart Phelps (1844-1911) was introduced to writing at a young age, as both her mother and father were published writers. In 1868 she published her first major novel, The Gates Ajar. An international success, the novel sold more than six hundred thousand copies, making it one of the best-selling American works of the nineteenth century. Through the next four decades Phelps published hundreds of essays, tales, and poems, which appeared in every major American periodical, while also writing novels, including Beyond the Gates (1883) and The Gates Between (1887). Phelps's legacy as an important American writer, however, has been hurt by the seeming contradictions between her life and work. For example, she was an ardent advocate for women's rights both inside and outside marriage, but her stories seem to glorify the sort of extreme self-sacrifice associated with the most conservative domestic ideology. In this collection, the editors seek to restore Phelps's reputation by bringing together a diverse collection from the entire body of her lifetime of work. From arguments for suffrage to harrowing tales of Reconstruction, these essays, along with short fiction and poetry, provide a new perspective on a major American writer from the later nineteenth century."--